Metal-Oxide-Based Nucleation Process under Confined Conditions: Two Mixed-Valence V6-Type Aggregates Closing the W48 Wheel-Type Cluster Cavities - Müller, Achim; Pope, Michael T.; Todea, Ana Maria; Bögge, Hartmut; van Slageren, Joris; Dressel, Martin; Gouzerh, Pierre; Thouvenot, René; Tsukerblat, Boris; Bell, Aidan (Angewandte Chemie International Edition, 2007)
Getting together helps: The wheel‐shaped P8W48 polyoxotungstate (see picture) provides a reaction chamber for the directed assembly of two unprecedented mixed‐valence vanadium oxide cavity‐capping groups based on linked octahedra and tetrahedra with VIV and VV centers, respectively. The magnetic and electronic properties are controlled by the confined conditions.